Monitoring Hydrological Processes for Land and Water Resources Management in a Mediterranean Ecosystem: The Alento River Catchment Observatory. Issue 1 (9th August 2018) - Romano, Nunzio; Nasta, Paolo; Bogena, Heye; De Vita, Pantaleone; Stellato, Luisa; Vereecken, Harry
Abstract : Core Ideas: Advanced sensor networks gather dense information on hydro‐meteorological variables. The Alento CZO helps assess the impact of climate and land‐use change on ecosystem services. Our research supports effective supply‐side and demand‐side adaptation strategies. In recent years, the critical zone (CZ) of catchments across the Mediterranean region has been influenced by rapid changes in both climate seasonality and land use–land cover. Rural ecosystems in southern Europe are experiencing prolonged droughts, seriously compromising water resource availability and crop yields while increasing the risk of wildfire occurrence. Rainy seasons are likely to be characterized by intense storms that trigger floods, resulting in increasing damage severity. The negative effects of anthropogenic disturbance on hydrological ecosystem services can be tempered by demand‐side adaptation options and appropriate investments to ensure water supply under drought conditions. To shed light on some of the scientific challenges related to these issues, a critical zone observatory (CZO) has been established in the Alento River catchment. Although sampling campaigns and monitoring investigations have been performed in this area for >25 yr, a more systematic research program was recently started to take comprehensive measurements in representative subcatchments of the study area. These sites are instrumented with advanced ground‐based sensor network platforms that provide hydro‐meteorological variables and fluxes in the groundwater–soil–vegetation–atmosphere system. Hydrological models of different complexity exploit the dense information gathered to assess the impact of land use and climate changes on key functions and services of the CZO in the Alento River catchment.